Primary splenic diffuse large B‐cell lymphoma presenting as a splenic abscess - Paul A. Wadsworth; Roberto N. Miranda; Pooja Bhakta; Peeyush Bhargava; Dylan Weaver; Jianli Dong; Vasily Ovechko; Michael Norman; Palawinnage V. Muthukumarana; Mathew G. Bayes; Jayati Mallick; Kirill A. Lyapichev (eJHaem, 2023)
Abstract Diffuse large B‐cell lymphoma (DLBCL) arising in the spleen, also known as primary splenic DLBCL (PS‐DLBCL), is a rare form of malignant lymphoma. It is defined as a lymphoma confined to the spleen or involving splenic hilar lymph nodes. Here we report a case of PS‐DLBCL with CD30. The patient was a 62‐year‐old who presented with 2 weeks of left flank pain, chills, and abdominal distension. Computed tomography identified an 8‐cm splenic mass with central necrosis interpreted as an abscess. A drain was placed, yielding purulent necrotic material; cytologically, only neutrophils were identified. However, purulent drainage continued for 28 days without resolution, prompting splenectomy. Pathological dissection revealed a multinodular mass with central necrosis. Microscopic examination revealed extensive karyorrhexis, abundant ghosts of large cells, and scattered large cells with pleomorphic, multilobated, and vesicular nuclei with moderately abundant cytoplasm. Immunohistochemical staining revealed large, atypical cells positive for CD20, CD30, CD45, PAX5, MYC (>40%), MUM1 (>30%), and p53 (focally). The large cells were negative for CD3 (polyclonal), CD4, CD5, CD8, CD10, CD15, CD34, BCL2, BCL6, AE1/AE3, S100, HHV8, and ALK. The Ki‐67 proliferation rate was approximately 80% in large cells. Notably, this PS‐DLBCL was positive for CD30, an unusual finding among non‐Hodgkin B‐cell lymphomas, which, coupled with the Reed‐Sternberg‐like morphology, raised the possibility of classic Hodgkin lymphoma. Therefore, we reviewed the literature to confirm the unique features of this large B‐cell lymphoma, its abscess‐like appearance, and its expression of CD30.